Penerapan Media Card Short Dalam Meningkatkan Keterampilan Berbicara Bahasa Arab: Studi Kasus Siswa Kelas VIII SMP Swasta Darul Qur’an Al-Maftuh Sungai Gelam, Muaro Jambi - Husna, Asmaul; Muid, Abdul; Vahlepi, Sahrizal (Al-Wazan: Journal of Arabic Education, 2024)
The development of science and technology, the power of teachers to improve education is getting stronger. Teachers have an important role in creating effective learning This research aims to find out whether the application of short card media can improve the Arabic speaking skills of class VIII students at SMPS Darul Qur'an Al-Maftuh Sungai Gelam, Muaro Jambi. This research was carried out at SMPS Darul Qur'an Al-Maftuh Sungai Gelam, Muaro Jambi. The research was carried out in January-February of the 2023/2024 academic year. This type of research is classroom action research (PTK). The data and data sources used in this classroom action research are observations, interviews, documentation and so on. This research is classroom action research (PTK), this classroom action research is action research carried out by teachers with the aim of knowing and improving the quality of implementation of learning in the classroom. The method used in this research is the classroom action practice research method (PTK). Based on the results of this research, the results of  student and teacher learning activities in cycle 1 reached a score of 78.09% and in cycle II it increased to a score of 83.98% and the increase in learning outcomes based on student test scores was the largest in cycle I, namely with a score of 76 and in cycle II got a score of 90, from each cycle the average score increased to 80,5. Based on the research results, it can be concluded that the application of Short card media improves the Arabic speaking skills of class VIII students at SMPS Darul Qur'an Al-Maftuh Sungai Gelam, Muaro Jambi. Proven to improve student learning outcomes